Identification of immunogenic cell death-related signature on prognosis and immunotherapy in kidney renal clear cell carcinoma - Jiang, Silin; Dong, Yuxiang; Wang, Jun; Zhang, Xi; Liu, Wei; Wei, Yong; Zhou, Hai; Shen, Luming; Yang, Jian; Zhu, Qingyi (Frontiers in Immunology, 2023)
Immunogenic cell death (ICD) is considered a particular cell death modality of regulated cell death (RCD). Increasing evidence has illustrated that ICD affect immune microenvironment and contribute to immunotherapy. ICD-targeted therapeutics may be beneficial to advanced and metastatic kidney renal clear cell carcinoma (KIRC) patients. In this study, we determined two ICD subtypes through consensus clustering analysis. The ICD-high subtype showed a better prognosis and higher level of immune infiltration. Furthermore, we constructed and validated an ICD prognostic signature to predict the overall survival of KIRC patients and subsequently analyzed the correlation of riskscore and immunotherapy. Our research focused on the function of ICD in KIRCand provided a novel insight into individualized immunotherapy.